An Evaluation of the Implementation of a “No Force First” Informed Organisational Guide to Reduce Physical Restraint in Mental Health and Learning Disability Inpatient Settings in the UK - Haines-Delmont, Alina; Goodall, Katie; Duxbury, Joy; Tsang, Anthony (Frontiers in Psychiatry, 2022)
Background: The use of physical restraint on vulnerable people with learning disabilities and mental health problems is one of the most controversial and criticized forms of restrictive practice. This paper reports on the implementation of an organizational approach called ‘No Force First’ within a large mental health organization in England, UK. The aim was to investigate changes in violence/aggression, harm, and physical restraint following implementation. Methods: The study used a pretest-posttest quasi-experimental design. Recorded incidents of violence/aggression from 44 inpatient mental health and learning disabilities (including forensic) wards were included (n= 13,599). Two study groups were created for comparison: the ‘intervention’ group comprising all incidents on these wards during the 24 months post-implementation (2018-2019) (n=6,551) and the ‘control’ group comprising all incidents in the 24 months preceding implementation (2015-2016) (n=7,048). Incidents recorded during implementation (i.e. 2017) were excluded (n=3,705). Incidence rate ratios (IRR) were calculated with 95% confidence intervals (95% CI). Multivariate regression models using generalized estimating equations were performed to estimate unadjusted and adjusted prevalence ratios (aPR) of physical restraint and harm, using type of wards, incident, and violence/aggression as key covariates. Results: A significant 17% reduction in incidence of physical restraint was observed [IRR = 0.83, 95% CI 0.77-0.88, p <.0001]. Significant reductions in rates of harm sustained and aggression/violence were also observed, but not concerning the use of medication during restraint. The prevalence of physical restraint was significantly higher in inpatients on forensic learning disability wards than those on forensic mental health wards both pre- (aPR = 4.26, 95% CI 2.91-6.23) and post-intervention (aPR = 9.09, 95% CI 5.09-16.23), when controlling for type of incident and type of violence/aggression. Physical assault was a significantly more prevalent risk factor of restraint use than other forms of violence/aggression, especially that directed to staff (not to other patients). Conclusions: This is a key study reporting the positive impact that organizational models and guides such as ‘No Force First’ can have on equipping staff to focus more on primary and secondary prevention as opposed to tertiary coercive practices such as restraint in mental health and learning disabilities settings.